Neoangiogenesis in the dynamics of testicular seminoma progression - S. M. Potapov; O. M. Pliten; N. I. Horhol (Kazimierz Wielki University, 2019)
Testicular germ cell tumors (TGCT) is a group of neoplasms which develop from the germ cell epithelium and account 94-96% of all testicular tumors. Seminoma is the most common testicular germ cell neoplasm and accounts for about 50% of all TGCT. There is an increasing evidence that metastatic disease in both early and late stages depends on the degree of tumor vascularization. But despite the large number of publications on this subject, the ways of new vessels formation in invasive neoplasms and effect of the intratumoral vessels density on overall and relapse-free survival rate remain unclear. The performed investigation of neoangiogenesis in the dynamics of testicular seminoma progression revealed: significant increasing of relative area of CD31 and CD34 expression as well as vascular density during transition from the initial to the late stages of tumor progression; formation of intratumoral vessels in the seminoma occurs by angiogenesis and vasculogenesis with participation of progenitor endothelial cells; seminoma is characterized by vasculogenic mimicry in the form of channels formation that do not have endothelial lining.